From Education Policy to Education Practice Unpacking the Nexus - Prøitz, Tine S.; Aasen, Petter; Wermke, Wieland (Policy Implications of Research in Education,, 2023)
This open access book addresses the complex interrelations between education policy and education practice developed under new ways of governance. It illuminates the nexuses of the interrelated fields of education policy and education practice including the characteristics of these relationships. The book offers a selection of cases with varied approaches to the question of how different actors and stakeholders are situated in contemporary policy and practice nexuses. The cases presented includes theoretical and conceptual studies; historical studies; ethnographic studies; and studies combining empirical interview data and quantitative data. The book shows what constitutes the contemporary nexuses in education and discusses the need to re-consider how we in education research approach policy and practice in the interface between structure and agency for the future developments in the education policy-practice nexus.